2017
DOI: 10.1007/s10067-017-3877-1
|View full text |Cite
|
Sign up to set email alerts
|

Altered frequencies of memory B cells in new-onset systemic lupus erythematosus patients

Abstract: Systemic lupus erythematosus (SLE) is a chronic systemic autoimmune disease, characterized by B cell hyperactivity and pathogenic autoantibodies formation. The objective of this study is to evaluate the distribution of B cell subsets in patients with SLE. We included patients with SLE followed in First Affiliated Hospital of Xi'an JiaoTong University, Xi'an, China. Flow cytometry was used to measure frequencies of B cell subsets, including memory B cells, switched memory B cells, non-switched memory B cells, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 26 publications
4
26
0
Order By: Relevance
“…Our study demonstrated that LN patients had significantly higher DN B cells than non-LN patients, suggesting that DN B cells are involved in the renal damage associated with SLE. This result is consistent with previous studies that showed DN B cells expanded in patients with LN (16,21). In addition, the levels of DN B cells were positively correlated to 24 h-UPE, suggesting that DN B cells may be involved in the severity of renal damage in LN patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study demonstrated that LN patients had significantly higher DN B cells than non-LN patients, suggesting that DN B cells are involved in the renal damage associated with SLE. This result is consistent with previous studies that showed DN B cells expanded in patients with LN (16,21). In addition, the levels of DN B cells were positively correlated to 24 h-UPE, suggesting that DN B cells may be involved in the severity of renal damage in LN patients.…”
Section: Discussionsupporting
confidence: 92%
“…It has been proposed that DN B cells are involved in the pathogenesis of SLE. DN B cells were reported to be correlated with anti-dsDNA and anti-RNP/Sm autoantibodies (19)(20)(21). However, the detailed clinical relevance of DN B cells in SLE remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…integrin in a subset of SLE patients, implying reduced potential for TS B cells to access GALT in these cases. Data presented here implicates GALT as an important site for MZB differentiation and MZB depletion has been reported in SLE (Rodriguez-Bayona et al, 2010;Zhu et al, 2018). Hence, we sought to determine whether our proposed MZB differentiation pathway was defective in SLE.…”
Section: Marginal Zone B Cell Differentiation Is Defective In Patientmentioning
confidence: 88%
“…DN2 cells may be derived from activated naïve B cells (aNAV), driven by TLR7 engagement, resulting in the generation of self-reactive antibody producing plasma cells (Jenks et al, 2018;Tipton et al, 2015). Interestingly, a recent study of a cohort of newly diagnosed patients with SLE demonstrated that MZB may be reduced in frequency (Zhu et al, 2018…”
Section: T Tsmentioning
confidence: 99%
“…The B cell repertoire has crucial pathogenic roles in LN which include synthesis of autoantibodies, presentation of autoantigens, and secretion of pro-inflammatory and anti-inflammatory mediators that regulate the immune response (29)(30)(31)(32)(33)(34)(35)(36). Accumulating evidence suggests that SLE is associated with perturbations in B lymphocyte subpopulations, epitomized by an expansion of class-switched memory B cells relative to naïve cells in active lupus patients compared to patients during disease quiescence (10,37,38). Changes in B cell subtypes pertaining to LN relapse, however, remain to be characterized.…”
Section: Discussionmentioning
confidence: 99%